Regenerative agriculture augments bacterial community structure for a healthier soil and agriculture - Singh, Indira; Hussain, Meeran; Manjunath, G.; Chandra, Nagasuma; Ravikanth, G. (Frontiers in Agronomy, 2023)
Introduction Use of chemical fertilization and pesticides not only harm the environment but also have detrimental consequences on human health. In recent years, there has been a major emphasis worldwide on natural agriculture methods. Regenerative agriculture is known across the world as a combination of nature-friendly farming practices such as no-till, cover cropping, crop-rotation, agroforestry and use of organic home-based/farm-based ingredients to revive soil health. In India, a number of farmers are slowly adopting these practices using home-based mixtures and farmyard manure for soil rejuvenation and pest management. In order to evaluate the efficacy of the regenerative agriculture practices, this study compared conventional and regenerative agriculture plots for their soil bacterial and nutrient profiles. Methods Two crops - ragi (Finger millet, an old world cereal eaten in India) and vegetable (tomato/beans), and different lengths (≤3 and >5 years) of regenerative practices were additional metrics considered to understand variabilities due to crop-type and period of application. The common regenerative agriculture practices used by farmers in this study included a mix of practices such as mulching, minimal-till, inter-cropping, crop-rotation, along with application of farmyard manure and other home-based concoctions rich in nutrients and microbes for enriching the soil. Results We found that all regenerative practices were effective in bringing about an enrichment for soil bacteria with a more heterogeneous composition. Additionally, in regenerative vegetable (RV) versus conventional vegetable (CV) and barren land (BL) plots the relative percentage abundance of Actinobacteriota (RV-7.47%/ CV-6.24%/BL -7.02%) and Chloroflexi (RV-9.37%/ CV-6.63%/BL-8.75%) was slightly higher. In contrast, levels of Acidobacteriota (RV-8.1%/ CV-9.88%/BL-9.62%) was significantly lower. Similarly, regenerative ragi (RR) in comparison with conventional ragi (CR) and barren land (BL) plots saw higher representation of Firmicutes (RR-5.45%/ CR-2.38%/BL-1.45%) and Actinobacteriota (RR-11.53%/ CR-7.08%/BL-7.15%) and a concurrent reduction in Acidobacteriota (RR-6.91%/CR-7.39%/ BL-9.79%). The RV plots were found to be enriched for Plant Growth Promoting Rhizobacteria (PGPRs) - Pseudomonas sp. (RV-0.51%/CV-0.01%/BL-0.21%), and RR plots were enriched for Bacillus sp. (RR-1.35%/CR-0.95%/BL-0.61%), and Mesorhizobium sp. (0.30%/0.12%/0.21%), which are known to play significant roles in vegetable and ragi growth respectively. Discussion Interestingly, long-term regenerative agriculture was able to support good nutrient composition while enhancing Soil Organic Carbon (SOC) levels. In all, the regenerative agriculture practices were found to be effective in improving bacterial community structure and simultaneously improving soil health. We found that BL soil with eucalyptus plantation showed among the least bacterial diversity suggesting detrimental impact on soil health.